2014
DOI: 10.15760/honors.38
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mycorrhizal Colonization and Light Limitation on Growth and Reproduction of Lima Bean (Phaseolus lunatus L.)

Abstract: SummaryPlants can respond with sink stimulation of photosynthesis when colonized with fungal or bacterial root symbionts, compensating costs of carbohydrate allocation to the microbes. However, constraints may arise under light limitation when plants cannot extensively increase photosynthesis. We hypothesize that under such conditions the costs for maintaining the symbiosis outweigh the benefits, ultimately turning the mutualist microbes into parasites, resulting in reduced plant growth and reproduction. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 48 publications
3
9
0
Order By: Relevance
“…If the metabolic energy to fix atmospheric N 2 is in short supply due to significant mycorrhizal C sink, which could be as high as 20% of the gross photosynthetic production (Jakobsen and Rosendahl, 1990), the benefits conferred to the host by rhizobia are actually hampered by the AM fungi. Although we do not have unequivocal evidence to show that this is happening, it is highly plausible, based also on previous experimental evidence showing additivity of C costs of the two microsymbionts in tripartite root symbioses (Paul and Kucey, 1981; Mortimer et al, 2008; Millar and Ballhorn, 2013; Ballhorn et al, 2016). Under high P availability or low light conditions, the coexistence of two root symbionts becomes a burden for the plant host (Ballhorn et al, 2016).…”
Section: Discussionmentioning
confidence: 85%
“…If the metabolic energy to fix atmospheric N 2 is in short supply due to significant mycorrhizal C sink, which could be as high as 20% of the gross photosynthetic production (Jakobsen and Rosendahl, 1990), the benefits conferred to the host by rhizobia are actually hampered by the AM fungi. Although we do not have unequivocal evidence to show that this is happening, it is highly plausible, based also on previous experimental evidence showing additivity of C costs of the two microsymbionts in tripartite root symbioses (Paul and Kucey, 1981; Mortimer et al, 2008; Millar and Ballhorn, 2013; Ballhorn et al, 2016). Under high P availability or low light conditions, the coexistence of two root symbionts becomes a burden for the plant host (Ballhorn et al, 2016).…”
Section: Discussionmentioning
confidence: 85%
“…). The ir CCaMK lines allowed us to test if the growth depressions of WT after AMF infection might result from (1) carbon drain by the fungus, as suggested in previous studies with infected lima beans that showed reduced fitness after shading (Millar & Ballhorn ), or (2) high P levels, which can also inhibit growth compared with non‐infected controls (Reynolds et al . ; Smith & Read ; Nouri et al .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to non-inoculating conditions, we also grew plants together with AM fungi because previous work showed that R. irregularis infected N. attenuata plants were smaller than non-infected plants when grown in the glasshouse (Riedel et al 2008). The irCCaMK lines allowed us to test if the growth depressions of WT after AMF infection might result from (1) carbon drain by the fungus, as suggested in previous studies with infected lima beans that showed reduced fitness after shading (Millar & Ballhorn 2013), or (2) high P levels, which can also inhibit growth compared with CCaMK silencing in N. attenuata non-infected controls (Reynolds et al 2005;Smith & Read 2008;Nouri et al 2014). However, our results are not consistent with either of these hypotheses: after inoculation with AMF, both WT and transgenic lines were reduced in growth, in particular under low P conditions ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it has been observed that sporulation in fungal cultures is reduced with shading (Morton et al, 1993). However, reductions in infection or investment in mycorrhizal fungi are not always detected (Hurst et al, 2002;Millar & Ballhorn, 2013). Moreover, previous work has not evaluated whether plants differentially reduce allocation to the most beneficial mutualist with shading or to the temporal responsiveness of plant allocation to shifts in light levels.…”
Section: Introductionmentioning
confidence: 99%